ANALYSIS OF SUSTAINABLE PROVISION OF EMPLOYMENT IN CONSTRUCTION IN THE NON-OIL SECTOR OF AZERBAIJAN - Elvin Ismayil oglu of Ajdarli (Foundations and Trends in Modern Learning, 2023)
Although the oil sector plays a leading role in the rapid economic development recorded in Azerbaijan in the last 10 years, the non-oil sector has been prominent in the overall economic growth in recent years. According to official statistics and macroeconomic indicators, the growth in the non-oil sector in the country was more than 2.2 times over the last 10 years. The strategy of spending oil revenues calculated on the diversification of the economy has been justified. Like any country in transition, Azerbaijan has benefited from its natural resources to build a strong economy, but it has been able to successfully diversify its economy and minimize its dependence on oil due to the income from these resources. As a result of this strategy, a continuous growth trend prevails in the construction, tourism, agriculture, transport, information and communication technologies sectors in the country.